Analisis Analisis Manajemen Logistik Bagian Pengadaan Alat Kesehatan Di Rumah Sakit Merangin Medical Centre Tahun 2024 - Irawan, Yeyen Gustina (ARUMAS, 2024)
Procurement is the activity of buying and receiving goods or services, this process starts from preparing what goods or services you want to buy to agreeing to make payments to third parties. The aim of this research is to analyze the logistics management of the medical equipment procurement department. This research uses a qualitative method using a systems approach through primary data collection carried out by interviews and observations with 5 respodent. The research results of the input components, warehouse and distribution facilities and infrastructure are sufficient space to store goods. The procedure uses the new 2019 SOP. The components of the procurement process and receiving process are safe when receiving goods. In the output component, the availability of medical equipment at Merangin Medical Center Hospital is sufficient. Keywords : Logistic Management, Procurement, Medical devices